Perbedaan Pemberian ROM Pasif Ekstremitas Bawah terhadap Bromage Score Pasien Post Operasi Sectio Caesarea dengan Spinal Anestesi - Happy Nurhayati; Cemy Nur Fitria; Wijayanti Wijayanti; Hasna A’ida Lutfi Nindita (Vitamin : Jurnal ilmu Kesehatan Umum, 2023)
Sectio caesarea is an act of removing the fetus and placenta through an incision in the abdominal wall and uterine wall in an intact state. Sectio caesarea is certainly inseparable from anesthesia, namely spinal anesthesia which will later use the bromage score as an indicator of anesthesia recovery. Range of Motion (ROM) can be interpreted as the maximum movement possible in a joint without causing pain. ROM is an important action that can affect the recovery of muscle movement after surgery. Purpose: To determine the difference in providing passive Range of Motion (ROM) of the lower extremities to the bromage score of patients after sectio caesarea surgery with spinal anesthesia. This study used a quasi-experimental research method (Quasi Experiment Method) with a Pre-post-test Design design with 15 respondents receiving intervention. Sampling with consecutive sampling. The test used was the Wilcoxon test. Data analysis using Wilcoxon with p = 0.005 (p <0.05). There is a difference in providing passive ROM of the lower extremities to the bromage score of patients after sectio caesarea surgery with spinal anesthesia.